Flame extension and the near field under the ceiling for travelling fires inside large compartments. (13th December 2019) - Heidari, Mohammad; Kotsovinos, Panagiotis; Rein, Guillermo
Summary: Structures need to be designed to maintain their stability in the event of a fire. The travelling fire methodology (TFM) defines the thermal boundary condition for structural design of large compartments of fires that do not flashover, considering near field and far field regions. TFM assumes a near field temperature of 1200°C, where the flame is impinging on the ceiling without any extension and gives the temperature of the hot gases in the far field from Alpert correlations. This paper revisits the near field assumptions of the TFM and, for the first time, includes horizontal flame extension under the ceiling, which affects the heating exposure of the structural members thus their load‐bearing capacity. It also formulates the thermal boundary condition in terms of heat flux rather than in terms of temperature as it is used in TFM, which allows for a more formal treatment of heat transfer. The Hasemi, Wakamatsu, and Lattimer models of heat flux from flame are investigated for the near field. The methodology is applied to an open‐plan generic office compartment with a floor area of 960 m 2 and 3.60 m high with concrete and with protected and unprotected steel structural members. The near field length with flame extension (fTFM) is found to be between 1.5 and 6.5 times longer than without flame extension. The duration of the exposure to peak heat flux depends on the flame length, which is 53 min for fTFM compared with 17 min for TFM, in the case of a slow 5% floor area fire. The peak heat flux is from 112 to 236 kW/m 2 for the majority of fire sizes using the Wakamatsu model and from 80 to 120 kW/m 2 for the Hasemi and Lattimer models, compared with 215 to 228 kW/m 2 for TFM. The results show that for all cases, TFM results in higher structural temperatures compared with different fTFM models (600°C for concrete rebar and 800°C for protected steel beam), except for the Wakamatsu model that for small fires, leads to approximately 20% higher temperatures than TFM. These findings mitigate the uncertainty around the TFM near field model and confirm that it is conservative for calculation of the thermal load on structures. This study contributes to the creation of design tools for better structural fire engineering.